2023
DOI: 10.1039/d3cc03002d
|View full text |Cite
|
Sign up to set email alerts
|

Homocoupling of benzyl pyridyl ethers via visible light-mediated deoxygenation

Jingtian Chen,
Fan Wang,
Xiang Li
et al.

Abstract: The challenging cleavage of C–O bonds in ethers was successfully accomplished through a visible light-mediated deoxygenation process of benzyl pyridyl ethers via their corresponding pyridinium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…White solid, yield: 78%, 62.4 mg; 1 H NMR (600 MHz, Chloroform- d ) δ 7.26 (d, J = 8.0 Hz, 4H), 7.08 (t, J = 8.0 Hz, 2H), 3.24 (s, 4H); 13 C­{ 1 H} NMR (151 MHz, Chloroform- d ) δ 136.8, 136.0, 128.3, 128.0, 29.8. The spectral data for this compound match that reported in the literature . HRMS (APCI), m / z : [M + H] + calcd.…”
Section: Methodssupporting
confidence: 78%
“…White solid, yield: 78%, 62.4 mg; 1 H NMR (600 MHz, Chloroform- d ) δ 7.26 (d, J = 8.0 Hz, 4H), 7.08 (t, J = 8.0 Hz, 2H), 3.24 (s, 4H); 13 C­{ 1 H} NMR (151 MHz, Chloroform- d ) δ 136.8, 136.0, 128.3, 128.0, 29.8. The spectral data for this compound match that reported in the literature . HRMS (APCI), m / z : [M + H] + calcd.…”
Section: Methodssupporting
confidence: 78%
“…We underline that, even though the BDEs of C–OAr bonds are remarkably low, almost no suitable method to utilize this feature in radical C–C bond formation reactions exists. Very recently, Yang reported that the C–O bond of 2-( N -methylpyridinium) benzyl ethers can be activated by a photoredox reaction to afford benzyl radical dimers . This indicates that even with such an elaborate and reactive leaving group the ether scope is restricted to benzylic ethers.…”
mentioning
confidence: 99%